Institutional change and shared management of water resources in large canal systems: results of an action research program in Pakistan - Bandaragoda, Don Jayatissa (International Water Management Institute, 1999)
Demonstrates the viability of farmers organizations for managing parts of the water resource system to achieve efficient and equitable use of water in a hierarchical society such as Pakistan. Suggests a successful conceptual and methodological framework for taking a bottom-up approach to the formation of water users associations and identifies possible constraints on its wider application.